Optimization of Water Distribution in Pagerwojo District Tulungagung, Indonesia, using Linear Programming Model - Ratih Indri Hapsari; Akhmad Suryadi; Affan Nurun Tajalla (Institute of Research and Community Outreach - Petra Christian University, 2022)
Optimization approaches has been utilized in solving complex water service problems. This study attempts to determine the optimal distribution system for clean water pipelines by applying linear programming method which enables the determination of the optimal and most affordable solution under all constraints. The decision variable was the water quantity allocated to the system. The piping investment, operational and maintenance costs in present value with 4% interest were calculated to obtain the water unit price. The allocated water should meet the requirements within a dependable discharge. The study was conducted in Pagerwojo District, Tulungagung Regency, Indonesia, grouped into three transmission lines with 106 l/s demand. There are three sources of fresh water, namely Song River, Klantur River, and Gondang Spring. The analysis reveals that the minimum cost was Rp456,679,296/month. Linear programming method is proven useful for determining the allocation of clean water in the most cost-efficient manner.